Ennis Friary
The soldiers, defeated by the Resurrection of Christ from the tomb, are in Norman armor, carrying the long spear and battle axe. Norman soldiers were mounted. They went through training which began in adolescence, and in tenth century Europe they had an unchallenged military supremacy. The Saxons did not fight from the saddle, but relied on defensive groups armed with spear , axe, and shield; in the battle, this method failed. The noble lady to the right is wearing court dress of a later period.